## Filters

Sort by :
Clear All
Q

4. Solve the following equations:

(a) 10p = 100

(b) 10p + 10 = 100

(c) p /4 = 5

(d) – p/3 = 5

(e) 3 p/4 = 6

(f) 3s = –9

(g) 3s + 12 = 0

(h) 3s = 0

(i) 2q = 6

(j) 2q – 6 = 0

(k) 2q + 6 = 0

(l) 2q + 6 = 12

(a) Divide both sides by 10, we get :                                (b) Transposing 10 to the RHS, we get :                              Now, dividing both sides by 10 gives  :        (c) Multiplying both sides by 4, we have :                               (d) Multiplying both sides by - 3 , we have  :                             (e) Multiplying both sides by , we have :                      ...

3. Give the steps you will use to separate the variable and then solve the equation:

(a) 3n – 2 = 46

(b) 5m + 7 = 17

(c) 20p / 3 = 40

(d) 3p/10 = 6

(a)   We have  3n – 2 = 46.         Transposing - 2 to the RHS, we have :                                   or                                 (b) We have      5m + 7 = 17         Transposing 7 to the RHS, we have :                                   or                                 (c) We have   20p / 3 = 40         Multiply both sides by   :                        or                         ...

2. Give first the step you will use to separate the variable and then solve the equation:

(a) 3l = 42

(b) b / 2 = 6

(c) p /7 = 4

(d) 4x = 25

(e) 8y = 36

(f) z/ 3 = 5 /4

(g) a /5 =7/ 15

(h) 20t = – 10

(a) Divide both sides by 3, we get :                                           (b) Multiply both sides by 2, we get :                                           (c) Multiply both sides by 7, we get :                                         (d) Divide both sides by 4, we get  :                                         (e) Divide both sides by 8, we get :                                      ...

1. Give first the step you will use to separate the variable and then solve the equation:

(a) x – 1 = 0

(b) x + 1 = 0

(c) x – 1 = 5

(d) x + 6 = 2

(e) y – 4 = – 7

(f) y – 4 = 4

(g) y + 4 = 4

(h) y + 4 = – 4

(a) Add 1 to both the sides, we have :                                 (b)  Transpoing 1 to the RHS, we have :                                  (c)  Transposing - 1 to the RHS, we have :                                 (d)  Transposing 6 to the RHS, we get :                                 (e) Transposing  - 4 to the RHS, we have :                                 (f) Transposing - 4 to  the...
Exams
Articles
Questions